Analisis Teknik Renang Gaya Bebas Pada Mahasiswa Mata Kuliah Renang Program Studi Penjaskesrek FKIP UIR - Rezki, Rezki; Jatra, Rices; SM, Nova Risma (Journal Sport Area, 2019)
This study aimed to know to what extent students’ skill of basic movement of freestyle swimming technique, the problem can be formulated as how are students’ mastery of basic swimming movement of freestyle swimming technique in Swimming course of Health, Physical Education and Recreation Department of Teacher Training and Education Faculty of Universitas Islam Riau. This study was descriptive design. There were 30 male students as participants of this research. The research result showed that there were 67% of students categorized as good level of freestyle swimming technique which 33% errors level.